Combining ethanol and cocaine exposure during adolescence increased cocaine reward sensitivity in adult rats as evaluated by a single exposure place preference paradigm - Colom-Rocha, Carles; García-Fuster, M. Julia (Frontiers in Pharmacology, 2025)
There is an urgent need for better understanding the long-term impact of polysubstance use initiation during adolescence. Our preclinical study examined the combined impact of ethanol and cocaine during a vulnerable window in adolescence on the long-term changes on cocaine reward emerging throughout withdrawal in adulthood. Male and female Sprague-Dawley rats were treated in adolescence with non-contingent paradigms of ethanol, cocaine, their combination or vehicle. Cocaine reward was assessed in adult rats, following prolonged withdrawal, by a simple paradigm based on a single exposure place preference previously characterized in mice, which was validated for Sprague-Dawley male and female adult rats. The main results demonstrated an increased impact of combining drugs (ethanol with cocaine) during adolescence on the outcome observed in adulthood, since a single exposure to cocaine increased the rewarding response induced by cocaine in these animals (i.e., increased time spent in the cocaine paired compartment). The combination of drugs during adolescence seemed to overcome that initial lack of response observed by just one of the drugs, thus presenting an augmented risk-factor for later consequences in adult rats of both sexes. To conclude, an early adolescent combined drug experience proved clear consequences on the emerging addictive-like behaviors observed in adulthood for both sexes.